(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The present paper is an attempt to analyse The Nicomachean Ethics of Aristotle in the context of the ongoing process of character formation. It explores the role of different types of Actions done by individuals in their character formation. It also critically analyses the limits and chal-lenges caused by the human surroundings and conditions in individuals’ life.